Health Service Utilization at West Sulawesi Provincial General Hospital - Aulia Apriliani; Nur Akifa Sartika Putri (International Journal Of Health Science, 2025)
In 2021, the number of outpatient visits at the West Sulawesi Provincial Hospital decreased by 46% compared to 2019, indicating a significant decline in the utilization of health services. This study aimed to analyze the factors related to the utilization of health facility services among outpatients. This quantitative research employed a cross-sectional design with a total of 100 respondents selected through accidental sampling. Data were collected using a structured questionnaire and analyzed using statistical tests to identify relationships between variables. The findings revealed that health insurance (p < 0.001) and affordability of access (p = 0.008) had a significant relationship with the utilization of health facility services. In contrast, knowledge (p = 0.075) and perception of pain (p = 0.055) were not significantly associated with service utilization. These results suggest that socioeconomic factors, particularly the ownership of health insurance and the accessibility of health services, play a crucial role in determining patients’ healthcare-seeking behavior. Therefore, efforts to improve health service utilization should focus on expanding insurance coverage, reducing access barriers, and ensuring the equitable availability of healthcare facilities in all regions.